STRATEGI INTERNATIONAL RIVERS DALAM PENANGANAN POTENSI KERUSAKAN LINGKUNGAN TERKAIT PEMBANGUNAN BENDUNGAN XAYABURI DI SUNGAI MEKONG, LAOS 2008-2016 - Widaloka, I Gusti Agung; Kumala Dewi, Putu Ratih; Widya Nugraha, A.A. Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2022)
ABSTRACT The Mekong River which has the second highest biodiversity in the world, is threatened by the planned construction of the Xayaburi Dam. The construction of the Xayaburi Dam threatens the diversity of the Mekong River ecosystem and the food security of millions of lao and Thai riverside villagers. The research method of this paper is qualitative descriptive. This research addresses the question of how International Rivers' strategy in dealing with the threat of environmental damage related to the construction of the Xayaburi Hydropower Dam on the Mekong River, Laos from 2008 to 2016. International Rivers applies the concept of transnational advocacy network strategy as a campaign movement strategy in dealing with the threat of damage to the construction of Xayaburi Dam. The data in this research were analyzed using transnational advocacy network strategy as campaign strategy of non-governmental international organization in international relations perspective. Keyword: International Rivers, Laos, Transnational Advocacy Strategy, Xayaburi Dam, Campaign